AI and the development of RD works - Hołda, Artur; Łojek, Paweł (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Artificial intelligence (AI) has become a tool increasingly used in scientific research, science, finance, and many other aspects of everyday life of entrepreneurs and every human being. This issue is developing extremely quickly and, according to the author of the article, its operation should be formalized and certain limits should be set to what it can be used for in order to eliminate unfair competition. The article presents the prospects for the development of AI in scientific research and financial management. Analysis and criticism of the literature was used as a research method.